2001
DOI: 10.4049/jimmunol.167.3.1283
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Paths for Activation of Naive CD8+ T Cells: CD4-Independent Help

Abstract: CD8+ CTLs play a pivotal role in immune responses against many viruses and tumors. Two models have been proposed. The “three-cell” model focuses on the role of CD4+ T cells, proposing that help is only provided to CTLs by CD4+ T cells that recognize Ag on the same APC. The sequential “two-cell” model proposes that CD4+ T cells can first interact with APCs, which in turn activate naive CTLs. Although these models provide a general framework for the role of CD4+ T cells in mediating help for CTLs, a number of is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 58 publications
5
73
0
Order By: Relevance
“…CD154 expression by alloantigen-stimulated CD4 T cells represents one such "help" mechanism promoting APC activation via CD40 (10,(13)(14)(15). However, CD8 T cells may respond to noninfectious Ags independent of CD4 help when Ag-specific precursors are present at high frequencies (16,17), or the affinity of Ag epitopes to MHC class I was high (18). Indeed, activation of cross-primed OVA-specific TCR-transgenic CD8 T cells became CD4 independent when increasing numbers of CD8 T cells were infused into class II-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…CD154 expression by alloantigen-stimulated CD4 T cells represents one such "help" mechanism promoting APC activation via CD40 (10,(13)(14)(15). However, CD8 T cells may respond to noninfectious Ags independent of CD4 help when Ag-specific precursors are present at high frequencies (16,17), or the affinity of Ag epitopes to MHC class I was high (18). Indeed, activation of cross-primed OVA-specific TCR-transgenic CD8 T cells became CD4 independent when increasing numbers of CD8 T cells were infused into class II-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…These DCs will further activate the majority of CD154-negative CD8 ϩ T cells. Indeed, a notion of CD8-self help in the context of CD4 help, has been recently introduced in antiviral model systems (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the widely studied suppressive activity of CD8 ϩ T cells, only recently was it demonstrated that CD8 ϩ T cells can also activate DCs and promote the Th1-and CTL-mediated type 1 immunity (21)(22)(23)(24)(25)(26)(27).…”
Section: Cd40l-expressing Cd4mentioning
confidence: 99%